Receptor-stimulated transamidation induces activation of Rac1 and Cdc42 and the regulation of dendritic spines. (1st May 2017) - Mi, Zhen; Si, Tuda; Kapadia, Khushboo; Li, Qian; Muma, Nancy A.
Abstract: Regulation of dendritic spines is an important component of synaptic function and plasticity whereas dendritic spine dysregulation is related to several psychiatric and neurological diseases. In the present study, we tested the hypothesis that serotonin (5-HT)2A/2C receptor-induced Rho family transamidation and activation regulates dendritic spine morphology and that activation of multiple types of receptors can induce transglutaminase (TGase)-catalyzed transamidation of small G proteins. We previously reported a novel 5-HT2A receptor downstream effector, TGase-catalyzed serotonylation of the small G protein Rac1 in A1A1v cells, a rat embryonic cortical cell line. We now extend these findings to rat primary cortical cultures which develop dendritic spines; stimulation of 5-HT2A/2C receptors increased transamidation of Rac1 and Cdc42, but not RhoA. Inhibition of TGases significantly decreased transamidation and activation of Rac1 and Cdc42, suggesting that transamidation led to their activation. In primary cortical cultures, stimulation of 5-HT2A/2C receptors by 1-(2, 5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI) caused a transient dendritic spine enlargement, which was blocked by TGase inhibition. Stimulation of both 5-HT2A and 5-HT2C receptors contributed to DOI-induced Rac1 transamidation in primary cortical cultures as demonstrated by selective antagonists. Furthermore, stimulation of muscarinic acetylcholine receptors and NMDA receptors also increased TGase-catalyzed Rac1 activation in SH-SY5Y cells and N2a cells, respectively. Receptor-stimulated TGase-catalyzed transamidation of Rac1 occurs at Q61, a site previously reported to be important in the inactivation of Rac1. These studies demonstrate that TGase-catalyzed transamidation and activation of small G proteins results from stimulation of multiple types of receptors and this novel signaling pathway can regulate dendritic spine morphology and plasticity. Graphical abstract: Highlights: Stimulation of 5-HT2A & 5-HT2C receptors transamidates and activates Rac1 and Cdc42. Stimulation of muscarinic acetylcholine and NMDA receptors activates Rac1. Activation of Rac1 & Cdc42 is reduced by inhibition or knock-down of transglutaminase. Receptor-stimulated transglutaminase-catalyzed transamidation of Rac1 occurs at Q61. 5-HT2A/C receptors induce transglutaminase-dependent dendritic spine size increases.